Pengabdian Masyarakat dengan “Deteksi Dini Kanker Payudara dengan SADARI” - Ana Setyowati; Pedvin Ratna Meikawati; Putri Andanawarih (LPPM Akbid Harapan Ibu Pekalongan, 2022)
Cancer is a disease that causes a lot of misery and death in humans. Breast cancer is the uncontrolled growth of cells in the breast. The emergence of these cancer cells occurs as a result of mutations or abnormal changes in genes that are responsible for maintaining cell growth and keeping it normal (healthy). Breast cancer can be detected early by means of breast selfexamination, clinical examination and mammography examination to find out early. BSE examination can be started early to become a routine habit in order to detect breast cancer early. The purpose of this service is to provide information about adolescent reproductive health, especially about early detection of breast cancer by conducting breast self-examination. The method used in this community service activity begins with the opening and introduction of the resource persons, then continues with the delivery of health education materials, a question and answer session to participants and finally closing. With this activity, the youth organizations find it helpful because young people have received information and supplies in detecting breast cancer from an early age.